2008
DOI: 10.1007/s00423-008-0402-7
|View full text |Cite
|
Sign up to set email alerts
|

Extended liver resection after preoperative chemotherapy: influence on regeneration and endoplasmic reticulum stress response

Abstract: It is concluded that CH leads to a delay in liver regeneration but is no contraindication for ischemia. On the contrary, CH seems to cause a preconditioning of livers leading to the induction of antiapoptotic chaperones in our short-term model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…What should be highlighted from our experiment is that we were able to slow down tumor growth in the liver without severely impairing liver growth following partial resection of the organ. Hepatic resection, probably because of all the growth factors it generates, stimulates the growth of any metastases remaining in the liver [ 53 , 54 ], and this undesired effect cannot be reverted by chemotherapy as it hinders liver recovery [ 55 , 56 , 57 ]. Administering curcumin prior to a partial hepatectomy could be an interesting approach when resecting liver metastases, as it could avoid the stimulus over dormant cancer cells or micrometastases remaining in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…What should be highlighted from our experiment is that we were able to slow down tumor growth in the liver without severely impairing liver growth following partial resection of the organ. Hepatic resection, probably because of all the growth factors it generates, stimulates the growth of any metastases remaining in the liver [ 53 , 54 ], and this undesired effect cannot be reverted by chemotherapy as it hinders liver recovery [ 55 , 56 , 57 ]. Administering curcumin prior to a partial hepatectomy could be an interesting approach when resecting liver metastases, as it could avoid the stimulus over dormant cancer cells or micrometastases remaining in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…The dose of 5-fluorouracil used, 20 mg/kg, is widely cited in studies of venous infusion in rats 21,22 and represents a bioequivalent dose in humans. Although chemotherapy in humans is performed through various applications at varying intervals depending on the scheme, the use of multiple doses in rats is difficult and is associated with high mortality 22,23 . Although the use of a single dose of chemotherapy may be considered insufficient to affect liver regeneration after hepatectomy, in the present study it was sufficient to significantly alter some parameters used to assess regeneration at two different time points after major hepatectomy.…”
Section: Discussionmentioning
confidence: 99%
“…A small number of experimental studies have assessed the effect of 5-fluorouracil in the neoadjuvant scenario, probably due to the relatively recent neoadjuvant administration scheme in humans. However, studies have proven the suppressive effect of liver regeneration when 5-fluorouracil is administered in the post-hepatectomy period 23,25,26 . Despite these findings, as well as those of Manekeller et al 23 , regarding the negative effects of preoperative administration of chemotherapeutic agents on the potential for liver regeneration, another study showed different results.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we chose a 1-week washout period before partial hepatectomy. In a rat model (18), liver regeneration was impaired after partial hepatectomy performed within 24 h of the last dose of chemotherapy. However, after such a short interval, liver regeneration is likewise impaired solely as direct inhibitory effects of the chemotherapy drugs on cell proliferation, as they inhibit cell growth both in vivo and in vitro (41), and does not mimic any clinical situation.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, an animal model could help in understanding this elusive topic. While impaired liver regeneration has been documented after a short interval after chemotherapy (within 24 h) (18), longer durations between chemotherapy and liver resection have not been studied in an animal model, yet. However, longer durations better represent the clinical situation Therefore, the aim of this study was to evaluate whether the most currently used drug regimens, including 5-FU, irinotecan, oxaliplatin or gemcitabine alone or in combination, may induce hepatocellular injury with a 1-week interval and to test whether these changes are associated with increased liver injury and impaired regeneration in non-tumoural liver parenchyma after hepatectomy.…”
Section: Introductionmentioning
confidence: 99%